Graft copolymer, production method of graft copolymer and use thereof

A graft copolymer with cellulose resin and polycarbonate addresses the limitations of conventional cellulose-based graft copolymers by maintaining resin performance and enhancing functional expression, achieving improved mechanical and thermal properties with reduced residue.

JP7603009B2Active Publication Date: 2024-12-19MURATA MFG CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021539257
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-09
Filing Date
2020-08-07
Publication Date
2024-12-19
Estimated Expiration
2040-08-07

AI Technical Summary

Technical Problem

Conventional graft copolymers using cellulose resin as a backbone polymer fail to maintain the performance level of cellulose-based resins while expressing the functions attributed to the graft portion, limiting their applicability.

Method used

A graft copolymer is developed with cellulose resin as the trunk polymer and polycarbonate as the branch polymer, with a specific mass proportion and molecular weight range, produced through copolymerization of epoxide and carbon dioxide or ring-opening polymerization of cyclic carbonate.

Benefits of technology

The graft copolymer maintains the performance of cellulose resin while exhibiting the functions of the graft portion, offering improved mechanical properties, thermal stability, and dispersibility, with reduced residue after thermal decomposition and enhanced moldability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603009000007
    Figure 0007603009000007
  • Figure 0007603009000008
    Figure 0007603009000008
  • Figure 0007603009000001
    Figure 0007603009000001
Patent Text Reader

Abstract

The present invention provides: a graft copolymer which leaves a little residue after thermal decomposition, while exhibiting excellent transparency and formability; a method for producing a graft copolymer; and a use of a graft copolymer. A graft copolymer according to the present invention has a backbone polymer and a branch polymer bonded to the backbone polymer; the backbone polymer contains a cellulose resin; and the branch polymer contains a polycarbonate. A method for producing a graft copolymer according to the present invention comprises: a step for performing a copolymerization of an epoxide and carbon dioxide in the presence of a cellulose resin; or a step for performing a ring-opening polymerization of a cyclic carbonate in the presence of a cellulose resin.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a graft copolymer, a method for producing the graft copolymer, and uses thereof. [Background technology]

[0002] Graft copolymers having a trunk polymer and a branch polymer bonded to the trunk polymer have been variously studied, and are highly valuable materials as novel functional resins that take advantage of the characteristics of both the trunk polymer and the branch polymer.

[0003] As such graft copolymers, materials having a structure in which a cellulose derivative is the trunk polymer and a vinyl polymer is the branch polymer are known. For example, Patent Document 1 proposes a graft copolymer obtained by dispersing cellulose fibers in water and radically polymerizing a vinyl monomer therein. In addition, Patent Document 2 proposes a graft copolymer obtained by grafting caprolactone or the like onto a cellulose resin, which is obtained by ring-opening polymerization of a cyclic ester compound in the presence of a cellulose derivative. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2009-67817 A [Patent Document 2] Japanese Patent Application Publication No. 59-86621 Summary of the Invention [Problem to be solved by the invention]

[0005] As described above, in a graft copolymer having a cellulose-based resin as a trunk polymer, it is expected that the function based on the characteristics of the graft portion will be expressed. However, on the other hand, the drawbacks of the cellulose-based resin remain unimproved, or the performance is inferior to that of the cellulose-based resin alone, and the conventional graft copolymers have not necessarily been able to eliminate the drawbacks of the cellulose-based resin. Due to such problems, the applications to which the conventional graft copolymers having a cellulose-based resin as a trunk polymer can be applied are limited. From this point of view, it is important that the graft copolymers having a cellulose-based resin as a trunk polymer have a certain level of performance of the cellulose-based resin while the function attributable to the graft portion is expressed.

[0006] The present invention has been made in view of the above, and aims to provide a graft copolymer in which a function attributable to the graft portion (trunk polymer portion) is expressed while a certain level of performance of a cellulose-based resin is maintained, a method for producing the graft copolymer, and uses thereof. [Means for solving the problem]

[0007] As a result of extensive research into achieving the above object, the present inventors have found that the above object can be achieved by using a cellulose-based resin as the trunk polymer and a polycarbonate as the branch polymer, thereby completing the present invention.

[0008] That is, the present invention includes, for example, the subject matter described in the following sections. Item 1 A graft copolymer having a trunk polymer and a branch polymer bonded to the trunk polymer, the trunk polymer comprises a cellulose-based resin, The graft copolymer, wherein the branch polymer comprises a polycarbonate. Section 2 Item 2. The graft copolymer according to item 1, wherein the proportion of the polycarbonate relative to the cellulose-based resin is 10% by mass or more and 300% by mass or less. Section 3 Item 3. The graft copolymer according to item 1 or 2, wherein the polycarbonate is an aliphatic polycarbonate. Section 4 Item 4. The graft copolymer according to item 3, wherein the aliphatic polycarbonate is at least one selected from the group consisting of polyethylene carbonate, polypropylene carbonate, and polytrimethylene carbonate. Section 5 5. The graft copolymer according to any one of items 1 to 4, wherein the cellulose-based resin is at least one selected from the group consisting of alkyl cellulose, hydroxyalkyl cellulose, and cellulose ester. Section 6 Item 6. The graft copolymer according to any one of items 1 to 5, wherein the cellulose-based resin is ethyl cellulose. Section 7 Item 7. The graft copolymer according to any one of items 1 to 6, having a mass average molecular weight of 50,000 or more and 1,000,000 or less. Section 8 A method for producing a graft copolymer, comprising a step of copolymerizing an epoxide and carbon dioxide in the presence of a cellulose-based resin. Section 9 A method for producing a graft copolymer, comprising a step of ring-opening polymerization of a cyclic carbonate in the presence of a cellulose-based resin. Section 10 Item 8. A paste composition comprising the graft copolymer according to any one of items 1 to 7. Section 10-1 Item 8. Use of the graft copolymer according to any one of items 1 to 7 in a paste composition. Section 11 8. A resin composition comprising the graft copolymer according to any one of items 1 to 7. Section 11-1 Item 8. Use of the graft copolymer according to any one of items 1 to 7 in a resin composition. Section 12 Item 8. A molded article comprising the graft copolymer according to any one of Items 1 to 7. Section 12-1 Item 8. Use of the graft copolymer according to any one of Items 1 to 7 in a molded article. Item 13 Item 8. An adhesive composition comprising the graft copolymer according to any one of items 1 to 7. Section 13-1 Item 8. Use of the graft copolymer according to any one of items 1 to 7 in an adhesive composition. Item 14 Item 8. An ink composition comprising the graft copolymer according to any one of Items 1 to 7. Section 14-1 Item 8. Use of the graft copolymer according to any one of items 1 to 7 in an ink composition. Item 15 Item 8. A coating composition comprising the graft copolymer according to any one of items 1 to 7. Section 15-1 Item 8. Use of the graft copolymer according to any one of items 1 to 7 in a coating composition. Section 16 Item 8. A binder resin comprising the graft copolymer according to any one of Items 1 to 7. Section 16-1 Item 8. Use of the graft copolymer according to any one of items 1 to 7 as a binder resin. Section 17 Item 8. A dispersant comprising the graft copolymer according to any one of Items 1 to 7. Section 17-1 Item 8. Use of the graft copolymer according to any one of Items 1 to 7 as a dispersant. Effect of the Invention

[0009] The graft copolymer according to the present invention exhibits functions attributable to the graft portion while maintaining a certain level of performance that the cellulose-based resin possesses. [Brief description of the drawings]

[0010] [Figure 1] 1H-NMR spectrum of the graft copolymer obtained in Example 1 in deuterated chloroform is shown. [Diagram 2] 1 shows an IR spectrum of the graft copolymer obtained in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the embodiments of the present invention will be described in detail. In this specification, the expressions "contain" and "include" include the concepts of "contain", "include", "consist essentially of" and "consist only of". In addition, in this specification, a numerical value connected with "~" means a numerical range including the numerical values ​​before and after "~" as the lower and upper limits.

[0012] 1. Graft copolymer The graft copolymer of the present invention has a trunk polymer and a branch polymer bonded to the trunk polymer, the trunk polymer containing a cellulose-based resin, and the branch polymer containing a polycarbonate. With such a graft copolymer, functions attributable to the graft portion are exhibited while a certain level of performance of the cellulose-based resin is maintained.

[0013] Here, the function attributable to the graft portion refers to, for example, excellent mechanical properties of a molded article containing the graft copolymer, excellent thermal decomposition properties of the graft copolymer, excellent thixotropy of a paste composition containing the graft copolymer, etc. Furthermore, the performance of the cellulose-based resin refers to, for example, spinnability when made into a paste composition, transparency when made into a molded article, and dispersion stability when used as a dispersion stabilizer.

[0014] In the graft copolymer of the present invention, the type of cellulose-based resin constituting the trunk polymer is not particularly limited, and for example, known cellulose-based resins can be widely applied. Specific examples of cellulose-based resins include alkyl celluloses such as methyl cellulose, ethyl cellulose, methylethyl cellulose, n-propyl cellulose, isopropyl cellulose, n-butyl cellulose, tert-butyl cellulose, and n-hexyl cellulose; hydroxyalkyl celluloses such as hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, and hydroxybutyl cellulose; cellulose esters such as cellulose acetate, cellulose diacetate, cellulose triacetate, cellulose acetate propionate, and cellulose acetate butyrate; carboxyalkyl celluloses such as carboxymethyl cellulose, carboxyethyl cellulose, and carboxypropyl cellulose; and cellulose derivatives or celluloses such as nitrocellulose, aldehyde cellulose, dialdehyde cellulose, and sulfonated cellulose. The type of cellulose-based resin constituting the trunk polymer can be one or more types.

[0015] Among these, from the viewpoint of superior thermal decomposition properties, the cellulose-based resin is preferably one or more selected from the group consisting of alkyl cellulose, hydroxyalkyl cellulose, and cellulose ester, more preferably alkyl cellulose, and particularly preferably ethyl cellulose.

[0016] In the graft copolymer of the present invention, the degree of substitution of the cellulose-based resin is not particularly limited and may be various values ​​as long as the effects of the present invention are not impaired. For example, the degree of substitution of the cellulose-based resin is 2 or more and 3 or less, and is generally 3.

[0017] In this specification, the degree of substitution of a cellulose-based resin refers to the total number of hydroxyl groups substituted with branch polymers out of all hydroxyl groups in the structural units of the cellulose-based resin.

[0018] The trunk polymer may contain structural units other than the cellulose-based resin, or may be formed only from the cellulose-based resin. When the trunk polymer contains structural units other than the cellulose-based resin, the content of such units may be 30% by mass or less, preferably 10% by mass or less, more preferably 5% by mass or less, and particularly preferably 1% by mass or less, based on the total structural units of the trunk polymer.

[0019] In the graft copolymer of the present invention, the branch polymer contains a polycarbonate. The polycarbonate is usually present by being chemically bonded to the cellulose resin, which is the trunk polymer. More specifically, in the graft copolymer of the present invention, the hydroxyl group or the hydrogen atom of the hydroxyl group in the structural unit of the cellulose resin is substituted with a polycarbonate.

[0020] The type of polycarbonate is not particularly limited, and for example, known polycarbonates can be widely applied. For example, the polycarbonate can be an aliphatic polycarbonate. In this case, the graft copolymer can be easily produced, and the graft copolymer can have less residue after pyrolysis and have better moldability.

[0021] In the graft copolymer of the present invention, when the polycarbonate is an aliphatic polycarbonate, the type thereof is not particularly limited, and it can be, for example, a structure having a structural unit represented by the following general formula (1).

[0022] [ka]

[0023] Here, in formula (1), R 1 , R 2 , R 3 and R 4 are the same or different and each represents a hydrogen atom, a linear or branched alkyl group having 1 to 10 carbon atoms which may be substituted with a substituent, or an aryl group having 6 to 20 carbon atoms which may be substituted with a substituent. 1 , R 2, R 3 and R 4 Two of these may be bonded to each other to form an aliphatic ring having 3 to 10 ring members which may be substituted by a substituent.

[0024] In formula (1), the linear or branched alkyl group having 1 to 10 carbon atoms is a linear or branched alkyl group having 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 carbon atoms. The number of carbon atoms in this alkyl group is preferably 1 to 4, and particularly preferably 1 or 2. Specific examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an n-hexyl group, an n-heptyl group, an n-octyl group, an n-nonyl group, and an n-decyl group.

[0025] In formula (1), when the linear or branched alkyl group having 1 to 10 carbon atoms is substituted with a substituent, the number of the substituents can be 1 or 2 or more. In this case, examples of the substituent include a hydroxyl group, an alkoxy group, an ester group, a silyl group, a sulfanyl group, a cyano group, a nitro group, a sulfo group, a formyl group, a carboxyl group, an aryl group, and a halogen atom (e.g., a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom). Examples of the alkoxy group include a methoxy group, an ethoxy group, an isopropoxy group, and a tert-butoxy group. Examples of the aryl group include a phenyl group, an o-tolyl group, an m-tolyl group, a p-tolyl group, and a naphthyl group.

[0026] In formula (1), the aryl group having 6 to 20 carbon atoms is an aryl group having 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20 carbon atoms. The number of carbon atoms in this aryl group is preferably 6 to 14. Examples of the aryl group include a phenyl group, a naphthyl group, and a tetrahydronaphthyl group.

[0027] In the formula (1), when the aryl group having 6 to 20 carbon atoms is substituted with a substituent, the number of the substituents can be 1 or 2 or more. In this case, examples of the substituent include an alkyl group, a hydroxyl group, an alkoxy group, an ester group, a silyl group, a sulfanyl group, a cyano group, a nitro group, a sulfo group, a formyl group, a carboxy group, an aryl group, and a halogen atom (e.g., a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom). Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, and a tert-butyl group. Examples of the aryl group include a phenyl group, an o-tolyl group, an m-tolyl group, a p-tolyl group, and a naphthyl group. Examples of the alkoxy group include a methoxy group, an ethoxy group, an isopropoxy group, and a tert-butoxy group.

[0028] In formula (1), R 1 , R 2 , R 3 and R 4 can be the same or may be partially or completely different. For example, in formula (1), R 1 , R 2 , R 3 and R 4 may all be the same, and R 1 , R 2 , R 3 are the same and R 4 may be different, R 1 , R 3 , R 4 are the same and R 2 may be different, R 1 , R 2 , R 3 , and R 4 may all be different.

[0029] In formula (1), R 1 , R 2 , R 3 and R 4 Two of these may be bonded to each other to form an aliphatic ring having 3 to 10 ring members which may be substituted by a substituent.1 , R 2 , R 3 , R 4 Two of the may be bonded to each other to form, together with the carbon atom to which they are attached, a substituted or unsubstituted, saturated or unsaturated aliphatic ring having 3 to 10 ring members. The aliphatic ring may be substituted with one or more substituents.

[0030] Examples of such an aliphatic ring include a 3- to 8-membered aliphatic ring that may be substituted with a substituent. More specifically, examples of the aliphatic ring include a cyclopentane ring, a cyclopentene ring, a cyclohexane ring, a cyclohexene ring, and a cycloheptane ring. In addition, when the aliphatic ring is substituted with a substituent, examples of the substituent include an alkyl group, an aryl group, an alkoxy group, an acyloxy group, an alkoxycarbonyl group, a silyl group, a sulfanyl group, a cyano group, a nitro group, a sulfo group, a formyl group, and a halogen atom (e.g., a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom). Examples of the alkyl group here include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, and a tert-butyl group. Examples of the aryl group include a phenyl group, an o-tolyl group, an m-tolyl group, a p-tolyl group, and a naphthyl group. Examples of the alkoxy group include a methoxy group, an ethoxy group, an isopropoxy group, a tert-butoxy group, etc. Examples of the acyloxy group include an acetoxy group, a propionyloxy group, a butyryloxy group, an isobutyryloxy group, a pivaloyloxy group, a benzoyloxy group, etc. Examples of the alkoxycarbonyl group include a methoxycarbonyl group, an ethoxycarbonyl group, a tert-butoxycarbonyl group, etc.

[0031] In formula (1), R 1 , R 2 , R 3 and R 4 are preferably the same or different and each is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. 1 , R 2 and R3 is a hydrogen atom, and R 4 is preferably a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. 4 More preferably, is a hydrogen atom, a methyl group, or an ethyl group.

[0032] In addition to the aliphatic polycarbonate having a structural unit represented by the formula (1), examples of the aliphatic polycarbonate include polytrimethylene carbonate, polytetramethylene carbonate, polyhexamethylene carbonate, poly-2,2-dimethyltrimethylene carbonate, and poly-1,4-cyclohexanedimethylene carbonate.

[0033] The branch polymer may be made of one or more types of polycarbonate.

[0034] In the graft copolymer of the present invention, the aliphatic polycarbonate which is the branch polymer is preferably at least one selected from the group consisting of polyethylene carbonate, polypropylene carbonate, and polytrimethylene carbonate. In this case, the graft copolymer is easy to produce, has less residue after thermal decomposition, and has better moldability and transparency. When the aliphatic polycarbonate is polyethylene carbonate, in the structural unit represented by formula (1), R 1 , R 2 , R 3 and R 4 is a hydrogen atom. When the aliphatic polycarbonate is polypropylene carbonate, in the structural unit represented by formula (1), R 1 , R 2 and R 3 is a hydrogen atom, and R 4 is a methyl group.

[0035] The polycarbonate constituting the branch polymer may have, for example, a structural unit other than that of formula (1), and may have a modified end group. Examples of structural units other than that of formula (1) include structural units such as polyether, polyester, polyamide, and polyacrylate, and structural units having reactive groups such as carboxyl groups, hydroxyl groups, and amino groups. Examples of modifications of end groups include modifications with acid anhydrides, cyclic acid anhydrides, acid halides, and isocyanate compounds. When the polycarbonate has a structural unit other than that of formula (1), the content thereof is preferably 10 mol % or less, more preferably 5 mol % or less, even more preferably 3 mol % or less, and most preferably 1 mol % or less, based on the total structural units of the polycarbonate.

[0036] In the graft copolymer of the present invention, the content ratio of the cellulose-based resin constituting the trunk polymer and the polycarbonate constituting the branch polymer is not particularly limited as long as the effects of the present invention are not impaired. From the viewpoint of less residue after thermal decomposition and more excellent moldability, the graft copolymer preferably has a polycarbonate ratio of 10% by mass or more and 300% by mass or less relative to the cellulose-based resin. In particular, the polycarbonate ratio of 50% by mass or more and 200% by mass or less relative to the cellulose-based resin is preferably.

[0037] The ratio of polycarbonate to cellulose-based resin can be determined by nuclear magnetic resonance spectroscopy (NMR analysis). In a graft copolymer, the ratio of polycarbonate to cellulose-based resin is also called the "graft ratio."

[0038] The mass average molecular weight of the graft copolymer of the present invention is not particularly limited, and can be, for example, 50,000 to 1,000,000. In this case, the graft copolymer can have better mechanical properties such as strength, elongation, and fracture toughness, and also has excellent moldability. The mass average molecular weight of the graft copolymer is more preferably 150,000 to 600,000.

[0039] The form of the graft copolymer of the present invention is not particularly limited, and may be in various forms depending on the application, such as powder, granules, lumps, pellets, strands, fibers, liquid, dispersion, solution, and molded body.

[0040] By making the graft copolymer of the present invention into the above-mentioned form, the residue after thermal decomposition is small, and the moldability and transparency are excellent, and in addition, the features of both the cellulose-based resin and the polycarbonate are well balanced. For example, the graft copolymer of the present invention has excellent spinnability and thixotropy when made into a solution, and therefore has excellent printability, and can be suitably used for applications such as paste, ink, and coating liquid. In addition, the molded product of the graft copolymer of the present invention has high transparency and exhibits excellent mechanical properties (mechanical strength and elongation), and therefore can be suitably used as a molded product such as a sheet or film. In addition, the graft copolymer of the present invention has excellent thermal decomposition properties as described above, and therefore can be suitably used as a thermally decomposable binder resin. Furthermore, the graft copolymer of the present invention has excellent dispersibility in various dispersion media, and can be suitably used as a dispersant.

[0041] The graft copolymer of the present invention is less susceptible to various problems associated with conventional graft copolymers using a cellulose-based resin as the trunk polymer, such as the problem of leaving a large amount of residue after thermal decomposition, the problem of the high transparency of the trunk polymer being difficult to achieve due to crystallization of the grafted portion, and the problem of not being able to maintain sufficient hardness for forming into a sheet.

[0042] 2. Method for producing graft copolymer The method for producing a graft copolymer of the present invention comprises a step of copolymerizing an epoxide with carbon dioxide in the presence of a cellulose-based resin. Alternatively, the method for producing a graft copolymer of the present invention comprises a step of ring-opening polymerization of a cyclic carbonate in the presence of a cellulose-based resin. Hereinafter, the production method comprising the former step will be referred to as "production method 1," and the production method comprising the latter step will be referred to as "production method 2." By production method 1 or production method 2, for example, the above-mentioned graft copolymer of the present invention is produced.

[0043] (Manufacturing method 1) In Production Method 1, epoxide and carbon dioxide are copolymerized in the presence of a cellulose-based resin. The cellulose-based resin used in Production Method 1 is a raw material for forming a trunk polymer of a graft copolymer. In Production Method 1, the polymer formed by copolymerization of epoxide and carbon dioxide is polycarbonate. In other words, the epoxide and carbon dioxide used in Production Method 1 are raw materials for forming a branch polymer of a graft copolymer.

[0044] The type of cellulose resin used in the manufacturing method 1 is not particularly limited, and for example, known cellulose resins can be widely applied. Specific examples of cellulose resins include alkyl celluloses such as methyl cellulose, ethyl cellulose, methylethyl cellulose, n-propyl cellulose, isopropyl cellulose, n-butyl cellulose, tert-butyl cellulose, and n-hexyl cellulose; hydroxyalkyl celluloses such as hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, and hydroxybutyl cellulose; cellulose esters such as cellulose acetate, cellulose diacetate, cellulose triacetate, cellulose acetate propionate, and cellulose acetate butyrate; carboxyalkyl celluloses such as carboxymethyl cellulose, carboxyethyl cellulose, and carboxypropyl cellulose; and cellulose derivatives or celluloses such as nitrocellulose, aldehyde cellulose, dialdehyde cellulose, and sulfonated cellulose. The cellulose resin used in the manufacturing method 1 can be one or more types.

[0045] From the viewpoint of superior thermal decomposition properties, the cellulose-based resin is preferably one or more selected from the group consisting of alkyl cellulose, hydroxyalkyl cellulose, and cellulose ester, more preferably ethyl cellulose, hydroxypropyl cellulose, and cellulose acetate butyrate, and particularly preferably ethyl cellulose.

[0046] The mass average molecular weight of the cellulose-based resin used in the production method 1 is not particularly limited. For example, the mass average molecular weight of the cellulose-based resin used in the production method 1 is preferably 5,000 or more, more preferably 10,000 or more, and even more preferably 100,000 or more. The mass average molecular weight of the cellulose-based resin used in the production method 1 is preferably 1,000,000 or less, more preferably 750,000 or less, and even more preferably 500,000 or less. The production method of the cellulose-based resin is not particularly limited, and for example, the cellulose-based resin can be produced by a known method. Alternatively, the cellulose-based resin used in the present invention can be obtained from a commercially available product, etc.

[0047] Examples of the epoxide used in the production method 1 include ethylene oxide, propylene oxide, trimethylene oxide (oxetane), 3,3-dimethyltrimethylene oxide, 1,2-butylene oxide, 2,3-butylene oxide, isobutylene oxide, 1-pentene oxide, 2-pentene oxide, 1-hexene oxide, 1-octene oxide, 1-dodecene oxide, cyclopentene oxide, cyclohexene oxide, styrene oxide, vinylcyclohexane oxide, 3-phenylpropylene oxide, 3,3,3-trifluoropropylene oxide, 3-naphthylpropylene oxide, 2-phenoxypropylene oxide, 3-naphthoxypropylene oxide, butadiene monoxide, 3-vinyloxypropylene oxide, and 3-trimethylsilyloxypropylene oxide. Among them, from the viewpoint of high reactivity, ethylene oxide, propylene oxide, trimethylene oxide and 1,2-butylene oxide are preferred, and ethylene oxide, propylene oxide and trimethylene oxide are more preferred. When the epoxide contains ethylene oxide, the resulting polycarbonate is polyethylene carbonate, when the epoxide contains propylene oxide, the resulting polycarbonate is polypropylene carbonate, and when the epoxide contains trimethylene oxide, the resulting polycarbonate is polytrimethylene carbonate.

[0048] In the production method 1, the polymerization reaction for copolymerizing the epoxide and carbon dioxide can also be carried out in the presence of a metal catalyst. Examples of the metal catalyst include zinc-based catalysts, aluminum-based catalysts, chromium-based catalysts, cobalt-based catalysts, etc. Among these, zinc-based catalysts and cobalt-based catalysts are preferred because they have high polymerization activity in the polymerization reaction of the epoxide and carbon dioxide.

[0049] Examples of zinc-based catalysts include diethylzinc-water catalyst, diethylzinc-pyrogallol catalyst, bis((2,6-diphenyl)phenoxy)zinc, N-(2,6-diisopropylphenyl)-3,5-di-tert-butylsalicylaldiminatozinc, 2-((2,6-diisopropylphenyl)amido)-4-((2,6-diisopropylphenyl)imino)-2-pentenezinc acetate, zinc adipate, and zinc glutarate.

[0050] Cobalt-based catalysts include cobalt acetate-acetic acid catalysts, N,N'-bis(3,5-di-tert-butylsalicylidene)-1,2-cyclohexanediaminocobalt acetate, N,N'-bis(3,5-di-tert-butylsalicylidene)-1,2-cyclohexanediaminocobalt pentafluorobenzoate, N,N'-bis(3,5-di-tert-butylsalicylidene)-1,2-cyclohexanediaminocobalt chloride, and N,N'-bis(3,5-di-tert-butylsalicylidene)-1,2-cyclohexanediaminocobalt nitride. tetraphenylporphyrin cobalt chloride, tetraphenylporphyrin cobalt acetate, N,N'-bis[2-(ethoxycarbonyl)-3-oxobutylidene]-1,2-cyclohexanediaminatocobalt chloride, and N,N'-bis[2-(ethoxycarbonyl)-3-oxobutylidene]-1,2-cyclohexanediaminatocobalt pentafluorobenzoate.

[0051] When using a cobalt catalyst, it is preferable to use a cocatalyst, such as pyridine, N,N-4-dimethylaminopyridine, N-methylimidazole, tetrabutylammonium chloride, tetrabutylammonium acetate, triphenylphosphine, bis(triphenylphosphoranylidene)ammonium chloride, and bis(triphenylphosphoranylidene)ammonium acetate.

[0052] The amount of the metal catalyst (co-catalyst if necessary) used in the polymerization reaction can be the same as the known copolymerization conditions of epoxide and carbon dioxide, and is preferably 0.001 mol or more, more preferably 0.005 mol or more, per mol of epoxide, from the viewpoint of promoting the progress of the polymerization reaction. The amount of the metal catalyst (co-catalyst if necessary) used in the polymerization reaction is preferably 0.2 mol or less, more preferably 0.1 mol or less, per mol of epoxide, from the viewpoint of obtaining an effect commensurate with the amount used.

[0053] A reaction solvent may be used in the polymerization reaction as necessary. The reaction solvent is not particularly limited, and various organic solvents can be used. Examples of the organic solvent include aliphatic hydrocarbon solvents such as pentane, hexane, octane, decane, and cyclohexane; aromatic hydrocarbon solvents such as benzene, toluene, and xylene; halogenated hydrocarbon solvents such as methylene chloride, chloroform, 1,1-dichloroethane, 1,2-dichloroethane, chlorobenzene, and bromobenzene; ether solvents such as dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, 1,3-dioxolane, and anisole; ester solvents such as ethyl acetate, n-propyl acetate, and isopropyl acetate; amide solvents such as N,N-dimethylformamide and N,N-dimethylacetamide; and carbonate solvents such as dimethyl carbonate, diethyl carbonate, and propylene carbonate.

[0054] The amount of the reaction solvent used is preferably 100 to 10,000 parts by mass per 100 parts by mass of the epoxide, from the viewpoint of smoothly proceeding with the reaction.

[0055] The method for polymerizing an epoxide and carbon dioxide in the presence of a metal catalyst is not particularly limited, but examples thereof include a method in which a cellulose-based resin, an epoxide, a catalyst, and optionally a co-catalyst, a reaction solvent, and the like are charged into an autoclave, mixed, and then carbon dioxide is injected to cause the reaction.

[0056] The amount of carbon dioxide used in the polymerization reaction is preferably 0.5 to 10 mol, more preferably 0.6 to 5 mol, and further preferably 0.7 to 3 mol, per mol of the epoxide.

[0057] In the polymerization reaction, the pressure of carbon dioxide is not particularly limited, but from the viewpoint of smoothly progressing the reaction, it is preferably 0.1 MPa or more, more preferably 0.2 MPa or more, and even more preferably 0.5 MPa or more, and from the viewpoint of obtaining an effect commensurate with the pressure used, it is preferably 20 MPa or less, more preferably 10 MPa or less, and even more preferably 5 MPa or less.

[0058] The polymerization reaction temperature in the polymerization reaction is not particularly limited, but from the viewpoint of shortening the reaction time, it is preferably 0° C. or higher, more preferably 20° C. or higher, and even more preferably 30° C. or higher, and from the viewpoint of suppressing side reactions and improving the yield, it is preferably 100° C. or lower, more preferably 80° C. or lower, and even more preferably 60° C. or lower.

[0059] The reaction time varies depending on the polymerization reaction conditions and cannot be generally determined, but it is usually preferably about 1 to 40 hours.

[0060] In the production method 1, the ratio of the cellulose-based resin to the epoxide used is not particularly limited and can be appropriately set depending on the desired graft ratio and the degree of substitution of the cellulose-based resin. From the viewpoint that the residue after thermal decomposition of the obtained graft copolymer is smaller and the copolymer is likely to have better moldability, the amount of the epoxide used is preferably 100 parts by mass or more and 5000 parts by mass or less, and more preferably 250 parts by mass or more and 2500 parts by mass or less, per 100 parts by mass of the cellulose-based resin.

[0061] As described above, by copolymerizing epoxide and carbon dioxide in the presence of a cellulose-based resin, the epoxide and carbon dioxide are polymerized to produce a polycarbonate, and the hydroxyl groups in the structural units of the cellulose-based resin also react with the epoxide. As a result, a graft copolymer having a structure in which the hydroxyl groups in the structural units of the cellulose-based resin or the hydrogen atoms of the hydroxyl groups are substituted with polycarbonate is obtained.

[0062] In the production method 1, after the polymerization reaction, the obtained graft copolymer can be purified by an appropriate method, if necessary.

[0063] (Manufacturing method 2) In production method 2, ring-opening polymerization of a cyclic carbonate is carried out in the presence of a cellulose-based resin. The cellulose-based resin used in production method 2 is a raw material for forming a trunk polymer of a graft copolymer. In addition, in production method 2, the polymer formed by the ring-opening polymerization of a cyclic carbonate is a polycarbonate. In other words, the cyclic carbonate used in production method 2 is a raw material for forming a branch polymer of a graft copolymer.

[0064] The type of cellulose-based resin used in Production Method 2 is not particularly limited, and examples include the same cellulose-based resins as those in Production Method 1. Therefore, the cellulose-based resin used in Production Method 2 is preferably one or more selected from the group consisting of alkyl cellulose, hydroxyalkyl cellulose, and cellulose ester, more preferably ethyl cellulose, hydroxypropyl cellulose, and cellulose acetate butyrate, and particularly preferably ethyl cellulose.

[0065] The type of cyclic carbonate used in the production method 2 is not particularly limited, and any known cyclic carbonate capable of forming a polycarbonate by ring-opening polymerization can be widely applied. Specific examples of cyclic carbonates include ethylene carbonate, propylene carbonate, trimethylene carbonate, 2,2-dimethyltrimethylene carbonate, 1,2-butylene carbonate, 2,3-butylene carbonate, isobutylene carbonate, cyclohexene carbonate, and tetramethylene carbonate. Among them, from the viewpoint of high reactivity, the cyclic carbonate is preferably ethylene carbonate, propylene carbonate, or trimethylene carbonate, and more preferably ethylene carbonate or propylene carbonate. When the epoxide comprises ethylene carbonate, the resulting polycarbonate is polyethylene carbonate; when the epoxide comprises propylene carbonate, the resulting polycarbonate is polypropylene carbonate; when the epoxide comprises trimethylene carbonate, the resulting polycarbonate is polytrimethylene carbonate.

[0066] In the production method 2, the method of ring-opening polymerization of the cyclic carbonate is not particularly limited, and known ring-opening polymerization conditions can be widely adopted. For example, the ring-opening polymerization of the cyclic carbonate can be carried out in the presence of a catalyst. Examples of the catalyst include metal catalysts such as sodium, potassium, sodium hydroxide, potassium hydroxide, triethylaluminum, aluminum triisopropoxide, n-butyllithium, titanium tetraisopropoxide, titanium tetrachloride, zirconium tetraisopropoxide, tin tetrachloride, sodium stannate, tin octanoate, and dibutyltin dilaurate; base catalysts such as pyridine, 4-dimethylaminopyridine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD), and 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU); acid catalysts such as methanesulfonic acid, trifluoromethanesulfonic acid, p-toluenesulfonic acid, diphenyl phosphoric acid, and phenol; and N-heterocyclic carbenes such as 1,3-bis(2-propyl)-4,5-dimethylimidazol-2-ylidene and 1,3-di-i-propylimidazol-2-ylidene. The catalyst used in the ring-opening polymerization may be one type alone or two or more types.

[0067] The ring-opening polymerization of cyclic carbonates can also be carried out using a cocatalyst, such as N-cyclohexyl-N'-phenylthiourea, N,N'-bis[3,5-bis(trifluoromethyl)phenyl]thiourea, N-[3,5-bis(trifluoromethyl)phenyl]-N'-cyclohexylthiourea, (-)-sparteine, etc.

[0068] The amount of catalyst (co-catalyst if necessary) used in the ring-opening polymerization of cyclic carbonate can be the same as the known ring-opening polymerization conditions of cyclic carbonate. From the viewpoint of promoting the progress of the polymerization reaction, it is preferably 0.001 mol or more, more preferably 0.005 mol or more, per 1 mol of cyclic carbonate. In addition, the amount of catalyst (co-catalyst if necessary) used in the polymerization reaction is preferably 0.2 mol or less, more preferably 0.1 mol or less, per 1 mol of cyclic carbonate, from the viewpoint of obtaining an effect commensurate with the amount used.

[0069] In the ring-opening polymerization of cyclic carbonate, a reaction solvent may be used as necessary. The reaction solvent is not particularly limited, but various organic solvents can be used. Examples of the organic solvent include aliphatic hydrocarbon solvents such as pentane, hexane, octane, decane, and cyclohexane; aromatic hydrocarbon solvents such as benzene, toluene, and xylene; halogenated hydrocarbon solvents such as methylene chloride, chloroform, 1,1-dichloroethane, 1,2-dichloroethane, chlorobenzene, and bromobenzene; ether solvents such as ethylene glycol dimethyl ether (monoglyme), diethylene glycol dimethyl ether (diglyme), triethylene glycol dimethyl ether (triglyme), dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, 1,3-dioxolane, and anisole; ester solvents such as ethyl acetate, n-propyl acetate, and isopropyl acetate; amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; and carbonate solvents such as dimethyl carbonate and diethyl carbonate.

[0070] The amount of the reaction solvent used is preferably 100 to 10,000 parts by mass per 100 parts by mass of the epoxide, from the viewpoint of smoothly proceeding with the ring-opening polymerization.

[0071] The ring-opening polymerization can be carried out, for example, by charging a cellulose-based resin, a cyclic carbonate, a catalyst, and optionally a co-catalyst, a reaction solvent, and the like into a glass flask, mixing them, and allowing them to react.

[0072] The reaction temperature for the ring-opening polymerization is not particularly limited, but from the viewpoint of shortening the reaction time, it is preferably 0°C or higher, more preferably 20°C or higher, and even more preferably 30°C or higher, and from the viewpoint of suppressing deterioration of the cellulose-based resin, it is preferably 250°C or lower, more preferably 200°C or lower, and even more preferably 180°C or lower.

[0073] The reaction time varies depending on the polymerization reaction conditions and cannot be generally determined, but it is usually preferably about 1 to 40 hours.

[0074] In the production method 2, the ratio of the cellulose resin to the cyclic carbonate is not particularly limited and can be appropriately set depending on the desired graft ratio and the degree of substitution of the cellulose resin. From the viewpoint that the residue after thermal decomposition of the obtained graft copolymer is smaller and the copolymer is likely to have better moldability, the amount of the cyclic carbonate used is preferably 100 parts by mass or more and 5000 parts by mass or less, and more preferably 200 parts by mass or more and 2000 parts by mass or less, per 100 parts by mass of the cellulose resin.

[0075] As described above, by carrying out ring-opening polymerization of the cyclic carbonate in the presence of the cellulose-based resin, the cyclic carbonate undergoes ring-opening polymerization to produce a polycarbonate, and the hydroxyl groups in the structural units of the cellulose-based resin also react with the cyclic carbonate. As a result, a graft copolymer having a structure in which the hydroxyl groups in the structural units of the cellulose-based resin or the hydrogen atoms of the hydroxyl groups are substituted with polycarbonate is obtained.

[0076] In the production method 2, after the polymerization reaction, the obtained graft copolymer can be purified by an appropriate method, if necessary.

[0077] The graft copolymers obtained by Production Method 1 and Production Method 2 are, for example, the above-mentioned graft copolymers of the present invention, and therefore have little residue after pyrolysis. Moreover, the graft copolymers obtained by Production Method 1 and Production Method 2 are also excellent in moldability and transparency.

[0078] 3. Uses and methods of using graft copolymers The graft copolymer of the present invention or the graft copolymer obtained by the production method of the present invention can be applied to various applications. For example, the graft copolymer can be used as a component of a paste composition, a resin composition, an adhesive composition, an ink composition, or a coating composition. In addition, a molded body can be formed from a material containing the graft copolymer. In addition, the graft copolymer can also be used as a binder resin, a dispersant, etc.

[0079] When the graft copolymer is used as a paste composition, the components other than the paste composition can be the same as those of a known paste composition. Examples of known paste compositions include conductive pastes and glass pastes that are widely used for various electronic materials and electronic components. Thus, the paste composition can contain, for example, the graft copolymer of the present invention, a solvent, and a conductive material, and examples of the conductive material include known metals such as gold, silver, copper, palladium, and nickel. The paste composition can also contain, for example, the graft copolymer of the present invention, a solvent, and a glass powder, and examples of the glass powder include silicon oxides such as CaO-Al2O3-SiO2, MgO-Al2O3-SiO2, and LiO2-Al2O3-SiO2; glass powders such as bismuth oxide glass, silicate glass, lead glass, zinc glass, and boron glass. The content of the graft copolymer in the paste composition can be the same as that of the resin component contained in a known paste.

[0080] When the graft copolymer is used as an adhesive composition, ink composition, or coating composition, the composition may be similar to each of the known compositions, except that the resin component is a graft copolymer.

[0081] When the graft copolymer is used as a molded product, the molding method is not particularly limited, and known molding methods and molding conditions can be widely applied. The shape of the molded product is also not particularly limited, and it can be in various shapes such as a sheet, film, plate, block, etc. In particular, the graft copolymer has excellent moldability, and it can be easily molded into a sheet or film, which was difficult with conventional graft copolymers.

[0082] When the graft copolymer is molded, the raw material used for molding may be the graft copolymer alone, or a raw material containing the graft copolymer and other resin materials may also be used.

[0083] When the graft copolymer is used as a binder resin, the binder resin may be the graft copolymer alone, or may contain other components in addition to the graft copolymer as long as the performance of the binder resin is not impaired. As described above, the graft copolymer leaves little residue after pyrolysis, so it can be suitably used as a binder resin intended to be burned off by pyrolysis.

[0084] When the graft copolymer is used as a dispersant, the dispersant may be the graft copolymer alone, or may contain the graft copolymer and other components to the extent that the performance of the dispersant is not impaired. As described above, the graft copolymer has excellent dispersibility in various dispersion media and can be suitably used as a dispersant. EXAMPLES

[0085] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the embodiments of these examples.

[0086] The mass average molecular weight (Mw) of the graft copolymer obtained in each of the Examples and Comparative Examples was measured by the following method. [Mass average molecular weight (Mw) of graft copolymer] A tetrahydrofuran solution with a graft copolymer concentration of 0.2% by mass was prepared, and the mass average molecular weight (Mw) of the graft copolymer was measured using a high performance liquid chromatograph (HPLC). The measured value was compared with that of polystyrene with a known mass average molecular weight measured under the same conditions, and the mass average molecular weight Mw of the graft copolymer was calculated. The measurement conditions were as follows: Column: GPC column (Shodex OHPac SB-804, SB-805, product name of Showa Denko K.K.) Column temperature: 40℃ Eluent: Tetrahydrofuran ·Flow rate: 1.0mL / min

[0087] (Production Example 1: Production of cobalt catalyst) In a 50 mL flask, 150 mg (0.25 mmol) of (R,R)-N,N′-bis(3,5-di-tert-butylsalicylidene)-1,2-cyclohexanediaminocobalt(II) (purchased from Aldrich), 53 mg (0.25 mmol) of pentafluorobenzoic acid, and 5 mL of methylene chloride were charged and stirred for 18 hours under air atmosphere. After removing the volatile components by distillation under reduced pressure, the mixture was dried under reduced pressure to obtain the cobalt complex as a dark green solid (yield 195 mg, 96%).

[0088] Example 1 In a 190 mL autoclave, 0.5 parts by mass of the cobalt complex obtained in Production Example 1, 0.4 parts by mass of bis(triphenylphosphoranylidene)ammonium chloride (PPNCl), and 30 parts by mass of ethyl cellulose (Mw=220,000, ethoxylation rate 48.0%) were charged, and the inside of the autoclave was replaced with a carbon dioxide atmosphere. Next, 120 parts by mass of propylene oxide were charged, and carbon dioxide was filled until the pressure inside the autoclave reached 1.0 MPa, and then the mixture was stirred at 40°C for 10 hours to obtain a reaction mixture. After the reaction was completed, the autoclave was depressurized, the reaction mixture was diluted with chloroform, and 30 parts by mass of hydrochloric acid-acidified methanol was added to stop the reaction. This mixture was concentrated under reduced pressure, and 100 parts by mass of chloroform was added to the obtained residue to dissolve it, and this solution was dropped into 2000 parts by mass of methanol to precipitate a solid. The obtained solid was filtered and dried at 70°C for 8 hours to obtain a graft copolymer. The resulting graft copolymer had a graft ratio of 200% by mass and Mw of 380,000.

[0089] Example 2 In a separable flask equipped with a cooling tube, a thermometer and a stirrer, 30 parts by mass of ethyl cellulose (Mw=220,000, ethoxylation rate 48.0%), 100 parts by mass of propylene carbonate, 1 part by mass of sodium stannate and 250 parts by mass of diglyme were charged. Then, the temperature was raised to 150°C under a nitrogen atmosphere, and the mixture was reacted by stirring at the same temperature for 24 hours. The resulting reaction solution was dropped into 1000 parts by mass of a 50% by mass aqueous methanol solution to precipitate a solid. The precipitated solid was collected by filtration, washed with 500 parts by mass of a 50% by mass aqueous methanol solution, and then dried at 70°C for 8 hours to obtain a graft copolymer. The resulting graft copolymer had a graft rate of 53% by mass and an Mw of 290,000.

[0090] Example 3 A graft copolymer was obtained in the same manner as in Example 2, except that 1 part by mass of sodium stannate was replaced with 0.5 parts by mass of tin octanoate and 0.5 parts by mass of 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD). The graft copolymer obtained had a graft rate of 90% by mass and Mw of 300,000.

[0091] Example 4 A graft copolymer was obtained in the same manner as in Example 2, except that 1 part by mass of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) was used instead of 1 part by mass of sodium stannate. The obtained graft copolymer had a graft ratio of 10% by mass and Mw of 250,000.

[0092] Example 5 In a separable flask equipped with a cooling tube, a thermometer and a stirrer, 30 parts by mass of ethyl cellulose (Mw=220,000, ethoxylation rate 48.0%), 100 parts by mass of ethylene carbonate, 0.2 parts by mass of sodium stannate and 250 parts by mass of diglyme were charged. Then, the temperature was raised to 150°C under a nitrogen atmosphere, and the mixture was reacted by stirring at the same temperature for 10 hours. The resulting reaction solution was dropped into 1000 parts by mass of a 50% by mass aqueous methanol solution to precipitate a solid. The precipitated solid was collected by filtration, washed with 1000 parts by mass of a 50% by mass aqueous methanol solution, and then dried at 70°C for 8 hours to obtain a graft copolymer. The resulting graft copolymer had a graft rate of 80% by mass and an Mw of 490,000.

[0093] Example 6 A graft copolymer was obtained in the same manner as in Example 5, except that 1 part by mass of sodium stannate was replaced with a combination of 0.1 part by mass of tin octanoate and 0.1 part by mass of TBD. The obtained graft copolymer had a graft ratio of 140% by mass and Mw of 520,000.

[0094] Example 7 A graft copolymer was obtained in the same manner as in Example 5, except that 0.2 parts by mass of DBU was used instead of 1 part by mass of sodium stannate. The obtained graft copolymer had a graft ratio of 40% by mass and Mw of 280,000.

[0095] Example 8 In a separable flask equipped with a cooling tube, a thermometer and a stirrer, 20 parts by mass of ethyl cellulose (Mw=220,000, ethoxylation rate 48.0%), 100 parts by mass of trimethylene carbonate, 1 part by mass of methanesulfonic acid and 250 parts by mass of diglyme were charged. Then, the temperature was raised to 60°C under a nitrogen atmosphere, and the mixture was reacted by stirring at the same temperature for 10 hours. The resulting reaction solution was dropped into 1000 parts by mass of a 50% by mass aqueous methanol solution to precipitate a solid. The precipitated solid was collected by filtration, washed with 500 parts by mass of a 50% by mass aqueous methanol solution, and then dried at 70°C for 8 hours to obtain a graft copolymer. The resulting graft copolymer had a graft rate of 250% by mass and an Mw of 680,000.

[0096] Example 9 In a separable flask equipped with a cooling tube, a thermometer and a stirrer, 30 parts by mass of hydroxypropyl cellulose (Mw=180,000), 60 parts by mass of propylene carbonate, 1 part by mass of dibutyltin dilaurate and 250 parts by mass of diglyme were charged. Then, the temperature was raised to 150°C under a nitrogen atmosphere, and the mixture was reacted by stirring at the same temperature for 24 hours. The resulting reaction solution was dropped into 1000 parts by mass of a 50% by mass aqueous methanol solution to precipitate a solid. The precipitated solid was collected by filtration, washed with 500 parts by mass of a 50% by mass aqueous methanol solution, and then dried at 70°C for 8 hours to obtain a graft copolymer. The resulting graft copolymer had a graft ratio of 70% by mass and an Mw of 270,000.

[0097] Example 10 A graft copolymer was obtained in the same manner as in Example 9, except that hydroxypropyl cellulose was replaced with cellulose acetate butyrate (Mw=90,000). The obtained graft copolymer had a graft ratio of 150% by mass and Mw of 210,000.

[0098] Comparative Example 1 A separable flask equipped with a cooling tube, a thermometer, and a stirrer was charged with 30 parts by mass of ethyl cellulose (Mw=220,000, ethoxylation rate 48.0%), 100 parts by mass of ε-caprolactone, and 55 parts by mass of xylene. The atmosphere was then replaced with nitrogen, and a solution in which 0.24 parts by mass of butyl titanate was dissolved in 30 parts by mass of xylene was added, heated to 145°C, and reacted at the same temperature for 14 hours with stirring. The resulting reaction solution was dropped into 1000 parts by mass of a 50% by mass aqueous methanol solution to precipitate a solid. The precipitated solid was collected by filtration, washed with 500 parts by mass of a 50% by mass aqueous methanol solution, and then dried at 70°C for 8 hours to obtain a graft copolymer. The resulting graft copolymer had a graft rate of 280% by mass and an Mw of 660,000.

[0099] (Reference example 1) Ethyl cellulose (Mw=220,000, ethoxylation rate 48.0%) was prepared alone.

[0100] FIG. 1 shows the results of the graft copolymer obtained in Example 1 in deuterated chloroform. 1 1 H-NMR spectrum of the graft copolymer obtained in Example 1, and FIG. 2 shows the IR spectrum of the graft copolymer obtained in Example 1.

[0101] Table 1 shows the production conditions for the graft copolymer of each Example, and the graft ratio and mass average molecular weight Mw of the obtained graft copolymer.

[0102] [Table 1]

[0103] These results demonstrated that the graft copolymer obtained in Example 1 had the desired structure.

[0104] (Evaluation example 1: Paste evaluation) The graft copolymers obtained in Examples 1 to 10, the graft copolymer obtained in Comparative Example 1, or the ethyl cellulose of Reference Example 1 were dissolved in toluene to a concentration of 3 mass % to prepare paste compositions. The spinnability and thixotropy of the obtained paste compositions were evaluated by the following methods.

[0105] <Evaluation of spinnability> A cylindrical rod made of polytetrafluoroethylene and having a diameter of 2.9 mm was immersed in a container containing the paste composition, and then the cylindrical rod was pulled up directly above the liquid surface at a speed of 5 mm / sec. At this time, the spinnability was measured from the outermost surface of the liquid surface to evaluate the spinnability.

[0106] <Thixotropy> Using a Brookfield viscometer (LVDV-I+ manufactured by Eiko Seiki Co., Ltd.), the viscosity of the paste composition was measured at a temperature of 25° C. and at rotation speeds of 5 rpm and 50 rpm. The ratio of the viscosity at a rotation speed of 5 rpm to the viscosity at a rotation speed of 50 rpm was calculated as the thixotropy index (TI value) and used as an index of thixotropy.

[0107] From the results of spinnability and thixotropy shown in Table 2, it can be determined that the graft copolymers obtained in each Example have excellent printability when made into a solution. Therefore, it can be said that the graft copolymers obtained in each Example are suitable for ink compositions, coating compositions, etc. in addition to paste compositions. On the other hand, the graft copolymer obtained in Comparative Example 1 generated gel-like insoluble components when made into a solution, and a uniform paste composition could not be obtained. Therefore, the results of Comparative Example 1 shown in Table 2 are listed as reference values, which are values ​​measured while insoluble components are still present.

[0108] [Table 2]

[0109] (Evaluation example 2: Film evaluation) The graft copolymer obtained in each Example, the graft copolymer obtained in Comparative Example 1, or the ethyl cellulose in Reference Example 1 was molded into a film having a thickness of 100 μm, and the transparency and mechanical strength were evaluated. The transparency was evaluated by measuring the haze value using a haze meter (Model 300A, manufactured by Nippon Denshoku Industries Co., Ltd.). The mechanical strength was evaluated by performing a tensile test at 25° C. and a speed of 50 mm / min using a tensile tester (Universal Tester ASG-J, manufactured by Shimadzu Corporation), and measuring the breaking stress and breaking strain.

[0110] From the results of the breaking stress and breaking strain shown in Table 3, it was found that the sheets of the graft copolymers obtained in the respective Examples exhibited excellent transparency, mechanical strength and elongation, and were shown to be suitable for use as sheets as well as molded articles such as films, etc. On the other hand, the graft copolymer obtained in Comparative Example 1 was excellent in mechanical strength and elongation, but had poor transparency, and was shown to be unusable for applications requiring transparency.

[0111] [Table 3]

[0112] (Evaluation Example 3: Thermal Decomposition Evaluation) The thermal decomposition initiation temperature and the amount of decomposition residue at 500°C were measured for the graft copolymer obtained in each Example, the graft copolymer obtained in Comparative Example 1, and the ethyl cellulose (Mw=220,000, ethoxylation rate 48.0%) in Reference Example 1. The thermal decomposition temperature and the amount of decomposition residue were measured by using a TG / DTA7220 manufactured by SII NanoTechnology Inc., and measuring the change in thermogravimetry while heating from room temperature (20°C) to 500°C at a heating rate of 10°C / min in an air atmosphere. The thermal decomposition initiation temperature was defined as JIS K7120:1987. Specifically, the temperature at the intersection of the line parallel to the horizontal axis passing through the mass before the start of the test heating and the tangent drawn so that the gradient between the bending points in the decomposition curve is maximized in the obtained decomposition curve was defined as the thermal decomposition initiation temperature. The amount of decomposition residue (decomposition residue rate) was calculated as the ratio of the amount of residue to the mass of the sample before the measurement based on the mass of the sample before and after the measurement.

[0113] From the results shown in Table 4, it was found that the graft copolymers obtained in each Example had excellent low-temperature decomposition properties and produced low residues. Therefore, it was shown that the graft copolymers obtained in each Example could be suitably used as thermally decomposable binder resins. On the other hand, the graft copolymer obtained in Comparative Example 1 had a high decomposition start temperature and produced a large amount of residues, and the graft copolymers obtained in the Examples were superior as binder resins.

[0114] [Table 4]

[0115] (Evaluation Example 3: Dispersibility Evaluation) 5 parts by mass of the graft copolymer obtained in each Example, the graft copolymer obtained in Comparative Example 1, or the ethyl cellulose of Reference Example 1, 20 parts by mass of silver particles (median particle size 0.5 μm by laser diffraction method), and 75 parts by mass of N-methylpyrrolidone were stirred at 150 rpm for 1 hour. The paste composition thus obtained was placed in a transparent cylindrical container, and the dispersion state was confirmed after 1 hour, 8 hours, and 24 hours. The case where the initial state was maintained by visual judgment was evaluated as A, the case where sedimentation occurred and less than 20% of the supernatant was observed was evaluated as B, and the case where more than 20% of the supernatant was observed was evaluated as C.

[0116] From the results shown in Table 5, it was found that the graft copolymers obtained in each Example had excellent dispersion stability. Therefore, it was shown that the graft copolymers obtained in each Example could be used as dispersants. On the other hand, the graft copolymer obtained in Comparative Example 1 was not able to obtain a homogeneous paste composition because a part of the graft copolymer became gelatinous and insoluble. When the evaluation was continued with the non-homogeneous paste composition, clear precipitation was confirmed after 2 hours, indicating that it is not suitable as a dispersant.

[0117] [Table 5]

Claims

1. A graft copolymer having a trunk polymer and a branch polymer bonded to the trunk polymer, the trunk polymer comprises a cellulose-based resin, The cellulose-based resin is at least one selected from the group consisting of alkyl cellulose and hydroxyalkyl cellulose, The graft copolymer, wherein the branch polymer comprises a polycarbonate.

2. The graft copolymer according to claim 1 , wherein the ratio of the polycarbonate to the cellulose-based resin is 10% by mass or more and 300% by mass or less.

3. The graft copolymer of claim 1 or 2, wherein the polycarbonate is an aliphatic polycarbonate.

4. 4. The graft copolymer according to claim 3, wherein the aliphatic polycarbonate is at least one selected from the group consisting of polyethylene carbonate, polypropylene carbonate and polytrimethylene carbonate.

5. The graft copolymer according to any one of claims 1 to 4, wherein the cellulose-based resin is ethyl cellulose.

6. The graft copolymer according to any one of claims 1 to 5, having a mass average molecular weight of 50,000 or more and 1,000,000 or less.

7. The method includes a step of copolymerizing an epoxide and carbon dioxide in the presence of a cellulose-based resin, The method for producing a graft copolymer, wherein the cellulose-based resin is at least one selected from the group consisting of alkyl cellulose and hydroxyalkyl cellulose.

8. A method for producing a graft copolymer, comprising a step of ring-opening polymerization of a cyclic carbonate in the presence of a cellulose-based resin.

9. A paste composition comprising a graft copolymer, The graft copolymer has a trunk polymer and a branch polymer bonded to the trunk polymer, the trunk polymer comprises a cellulose-based resin, A paste composition, wherein the branched polymer comprises a polycarbonate.

10. A resin composition comprising the graft copolymer according to any one of claims 1 to 6.

11. A molded article comprising the graft copolymer according to any one of claims 1 to 6.

12. An adhesive composition comprising the graft copolymer according to any one of claims 1 to 6.

13. An ink composition comprising a graft copolymer, comprising: The graft copolymer has a trunk polymer and a branch polymer bonded to the trunk polymer, the trunk polymer comprises a cellulose-based resin, The ink composition, wherein the branched polymer comprises a polycarbonate.

14. A coating composition comprising the graft copolymer according to any one of claims 1 to 6.

15. A binder resin comprising the graft copolymer according to any one of claims 1 to 6.

16. A dispersant comprising a graft copolymer, comprising: The graft copolymer has a trunk polymer and a branch polymer bonded to the trunk polymer, the trunk polymer comprises a cellulose-based resin, The dispersant, wherein the branched polymer comprises a polycarbonate.

Citation Information

Patent Citations

  • Production of new graft polymer

    JP1984086621A

  • Diazo type copying material

    JP1985225843A

  • Composition containing polyanionic polysaccharide and hydrophobic bioabsorptive polymer

    JP1996208706A

  • Modification of amines and alcohols

    JP2008525571A

  • Fiber-reinforced composite material and method for producing the same

    JP2009067817A